2004
DOI: 10.1093/hmg/ddh321
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections of CLN3, Hook1 and Rab proteins link Batten disease to defects in the endocytic pathway

Abstract: The endosomal/lysosomal transmembrane protein CLN3 is mutated in the Batten disease (juvenile neuronal ceroid lipofuscinosis, JNCL). However, the molecular mechanism of JNCL pathogenesis and the exact function of the CLN3 protein have remained unclear. Previous studies have shown that deletion of BTN1, the yeast orthologue of CLN3, leads to increased expression of BTN2. BTN2 encodes Btn2p, a proposed homologue to a novel microtubule-binding protein Hook1, which regulates endocytosis in Drosophila. We analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 54 publications
6
125
1
2
Order By: Relevance
“…A recent report indicates that, similar to yeast cells, arginine transport into lysosomes is defective in JNCL patient-derived lymphoblasts (Ramirez-Montealegre and . Other studies with human fibroblasts indicate CLN3 involvement in lysosomal pH maintenance and degradation (Golabek et al, 2000) and endocytosis (Luiro et al, 2004). Cells derived from Cln3 ⌬ex7/8 mice display defects in endosome-to-lysosome vesicular trafficking and mitochondrial function (Fossale et al, 2004), and microarray analysis of neurons from Cln3 ⌬ex7/8 mice reveals altered levels of transcripts coding for proteins involved in synaptic, cytoskeletal, and metabolic functions (Luiro et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicates that, similar to yeast cells, arginine transport into lysosomes is defective in JNCL patient-derived lymphoblasts (Ramirez-Montealegre and . Other studies with human fibroblasts indicate CLN3 involvement in lysosomal pH maintenance and degradation (Golabek et al, 2000) and endocytosis (Luiro et al, 2004). Cells derived from Cln3 ⌬ex7/8 mice display defects in endosome-to-lysosome vesicular trafficking and mitochondrial function (Fossale et al, 2004), and microarray analysis of neurons from Cln3 ⌬ex7/8 mice reveals altered levels of transcripts coding for proteins involved in synaptic, cytoskeletal, and metabolic functions (Luiro et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The function of CLN3 protein remains unknown, however, recent studies have suggested a role for CLN3 in cellular transport (Fossale et al, 2004;Luiro et al, 2004;Weimer et al, 2005). Therefore, loss of CLN3 may affect not only the intracellular transport of various cargos, but the communication between neuronal populations.…”
Section: Discussionmentioning
confidence: 99%
“…Further circumstantial evidence comes from the fact that both RIM-BP1 and RIM-BP2, the two highly conserved parologs that are expressed in the brain, are involved in vesicle transport in neuronal cells (Hibino et al, 2002). Finally, both RIM-BP3 interacting partners Hook1 and KIF3B have been connected with Rab proteins involved in endocytosis (Imamura et al, 2003;Luiro et al, 2004). All these proteins, including RIM-BP3, Hook1, Kinesins, RIMs and Rabs, seem to be networked for complex intracellular trafficking and transport.…”
Section: Research Articlementioning
confidence: 99%